Mitigation-Based Assistance Project For Strengthening Pancasila Student Profile (P5) to Realize Independent Learning at Sukodadi 2 Elementary School, Bandongan District - Rasidi, Rasidi; Bimantoro, Madani Eko; Karnia, Fita Tri; Nugraheni, Aji; Kinanti, Ofika Putri; Aji, M Ardha Bawono Seto (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The 2013 curriculum change to an independent curriculum with the concept of independent learning provides many conveniences for teachers and students to learn according to their talents, interests and potential. What is new is related to the project to strengthen the pancasila student profile (p5), where not all schools fully understand the concept of the project desired by the government. Teachers need to understand the importance of projects; project planning needs to be more optimal, assistance from related agencies is not optimal, and projects are still product-oriented, not process oriented. These problems were then accommodated, and needed intervention from outsiders, one of which was from the integrated community service team (ppmt). The implementation methods used in this service are team-based projects for strategic project steps, brainstorming and focus group discussions in preparing instruments, experiential learning in project assistance, and exploratory data analysis in project reflection. The results of the service in terms of the quality of the service are carried out well, and the sustainability of this program leads to the development and independence of teachers in optimizing projects. This service is carried out for schools that independently implement an independent curriculum and solve problems in planning, implementing, and evaluating projects. The project's continuation to strengthen pancasila students' profile can be continued through changes in mindset, collaboration, and a community of practitioners.